Pembuatan Aplikasi Manajemen Organisasi Swara (AMORA) Berbasis Desktop - Rouf, Abdur (Technomedia Journal, 2019)
The use of technology is very important for updates in data management of an organization, especially in the current digital era. The development of information technology is happening very fast. Every time new technologies emerge that add value to existing technologies. Based on all the advantages that can be obtained with the existence of computer technology, researcher are interested to develop an application that will be used for management of organizational membership, and the activities of the work program scheduled. This application development utilizes java programming with a MySQL database. The system development method used in this study is to follow the stages of SDLC (System Development Life Cycle). The author uses the waterfall model because the execution of a system is done sequentially or linearly. The steps taken in developing applications in this study are System Requirement Analysis, System Design, and Encoding. This study successfully developed a Desktop-based SWARA Organization Management Application (AMORA) that can automate the process of recording organizational membership data, divisions and organizational agendas so that it can facilitate organizational data management. Keywords: Application, Management, Organization, Desktop